In silico Identification of miRNA as possible therapeutic targets for Micro Invasive Bladder Cancer (MIBC) treatment - Leitón Arrieta, Sylvia (2023)
Urothelial bladder cancer is the fourth most common malignancy in incidence in men, ranking eighth in mortality; while in women it is not in the top 10 in incidence or mortality. Advanced age is the main risk factor, with a median age at diagnosis between 70 and 84 years, with women 3 to 4 times less at risk than men. This is traditionally attributed to exposure and lifestyle, the use of carcinogens such as tobacco smoke, and exposure to carcinogenic aromatic amines is the second most important risk factor, representing (dyes, rubbers, textiles, paints and leathers) the second highest risk factor. Micro-invasive bladder cancer (MIBC) requires patients to undergo long-term invasive surveillance with diagnostic and therapeutic cystoscopy. The treatment of MIBC is undergoing rapid changes, as immunotherapy with checkpoint inhibitors, targeted therapies and antibody conjugates have become possible therapeutic options, and the identification of potential therapeutic targets with miRNAs is of increasing research interest.